Soil nutrient heterogeneity affects the accumulation and transfer of cadmium in Bermuda grass (Cynodon dactylon (L.) pers.). (April 2019) - Chen, Bin; Tan, Shuduan; Zeng, Qingru; Wang, Andong; Zheng, Huabin
Abstract: There have been no studies demonstrating the correlation between soil nutrient heterogeneity and cadmium (Cd) absorption of Bermudagrass. In this study, a pot experiment was carried out to study the correlation between them. The purpose is to find soil nutrient factors which are conducive to improving the Cd absorption and translocation. The eighth group had the largest total number of surviving plants, the highest Fv/Fo value (3.24) and the best growth characteristics. The fifth group had the lowest total number of surviving plants, Fv/Fo (2.47) and the worst growth. The Cd content of the fifth group (36.11 mg kg −1 ) was close to the eighth group (35.72 mg kg −1 ), but the two groups had significant differences in plant height, stem node length and stem node number (P < 0.05). The eighth group showed the highest contents of nitrate nitrogen (NO3 − -N), available potassium and urease activity. The fifth group showed the lowest NO3 − -N content, but the highest ammonium nitrogen (NH4 + -N) and available phosphorus content. There was significant difference of the Cd bioconcentration factors (BCF) and translocation factor (TCF) between the fifth and the eighth group although they had the similar total soil Cd content (P < 0.05). The fifth group had the highest BCF and TCF. RDA analysis indicated the BCF and TCF were positively correlated with soil NH4 + -N and available phosphorus and negatively correlated with soil NO3 − -N. The results demonstrated that soil NH4 + -N and available phosphorus were important soil ecological factors to enhance Cd absorption and translocation of bermudagrass. Highlights: Bermudagrass has great potential in the remediation of Cd contaminated soil. Soil nutrient heterogeneity affected bermudagrass growth and Cd absorption. BCF and TCF were positively correlated with soil available phosphorus and NH4 + -N. Soil available P and NH4 + -N contents enhanced Cd enrichment of bermudagrass.